National clinical practice guidelines for allergen immunotherapy: An international assessment applying AGREE‐II. Issue 3 (17th October 2017) - Larenas‐Linnemann, D. E. S.; Antolín‐Amérigo, D.; Parisi, C.; Nakonechna, A.; Luna‐Pech, J. A.; Wedi, B.; Davila, I.; Gómez, M.; Levin, M.; Ortega Martell, J. A.; Klimek, L.; Rosario, N.; et al.
Abstract: Background: Since 1988, numerous allergen immunotherapy guidelines (AIT‐GLs) have been developed by national and international organizations to guide physicians in AIT. Even so, AIT is still severely underused. Objective: To evaluate AIT‐GLs with AGREE‐II, developed in 2010 by McMaster University methodologists to comprehensively evaluate GL quality. Methods: Allergist, from different continents, knowledgeable in AIT and AGREE‐II trained were selected into the project team. The project received methodologists' guidance. AIT‐GLs in any language were sought from 1980 to 2016; AIT‐GLs were AGREE II‐evaluated by at least 2 team members, independently; discrepancies were resolved in a second round, by team discussion or methodologists' consulting. Results: We found 31 AIT‐GLs (15 post‐2010), ranging from local consensus reports to international position papers (EAACI, AAAAI‐ACAAI, WAO). Pre‐2010 GLs scored 1.6‐4.6 (23%‐67%) and post‐2010 GLs scored 2.1‐6 (30%‐86%), on a 7‐point Likert scale. The highest scores went to: German‐Austrian‐Swiss (6.0), Mexican (5.1), and the AAAAI/ACAAI AIT‐GL (4.7). These were also the only 3 GLs that received "yes" of both evaluators to the item: "I would recommend this GL for use." The domains of "Stakeholder involvement" and "Rigor of Development" only scored 3/7, and "Applicability" scored the lowest. Strikingly, newer GLs only scored clearly better in "Editorial independence" and "Global evaluation." Conclusions: In AIT‐GLs, there is still a lot of room for improvement, especially in domains crucial for the dissemination. For some GLs, the "Scientific rigor" domain flawed. When resources are limited, transculturizing a high‐quality GL might be preferable over developing a GL from zero. Our study and AGREE‐II could help to select the best candidate. Clinical Implications: We here evaluate allergen immunotherapy guideline (AIT‐GL) quality. Only high‐quality AIT‐GLs should be consulted for AIT management decisions. In low‐resource settings, transculturization of these is preferred over developing low‐quality guidelines.